O agravo de petição como provimento recursal adequado para impugnar sentenças, decisões interlocutórias e despachos-decisórios na execução trabalhista - BENTES, José Edílsimo Eliziário (Universidade Federal do Pará, 2015)
The central idea came due to professional activity. Observing in the day by day the difficulty of those who, unconformed with an act practiced in the phase of execution of a labour process, don’t find, with the desired security, an adequated judicial providence to submit the appreciation of such act to a college decision. Appeal against judgment is suitable, in a period of 8 (eight) days, from the Judge’s or President’s decisions, in the executions. This is what says the specific legislation. One serious problem in the interpretation of this command is to know what are “decisions” taken in the laboural execution, which can be refuted through appeal against judgment. This problematic is found inside a whole processual context, and that’s why we had to follow an outline starting by basic notions of process as instrument used by the State for the exercise of its jurisdictional function. From general to particular, we got into labour process and its phases, attaching to the execution one, how it begins and finishes. The main issue is the reaction to the execution, the reactionning means, specially the appeal as a consequence of the principle of double level of jurisdiction, being or not a constitutional guarantee. According to legal prevision, such appeal is the appeal against judgment. We talk about it and about the acts which the judge can practice in labour execution, saying the nature of each one of them. We also talk about interlocutory decisions, registering our worry with the difficulty we have in identifying them, mainly in the phase of execution. In the final part of this work, we deal with the question of possibility or not of using appeal against interlocutory decision, illustrating this study with some examples based on real cases and the solutions given to each of them.